Micro/nanoscale biochar facilitates cadmium immobilization and soybean resilience: Insights from microbial life-history strategies and plant physiological response - Yaping Wang; Yichen Xu; Yini Cao; Yi Hu; Changrui Liu; Chuanxin Ma; Wende Yan (Bioresource Technology, 2026)

Prokaryotic community diversity, assembly processes, and potential metabolic pathways of a hexanoic acid-producing microbiota constructed from Chinese baijiu fermentation pit mud - Xiaolong Hu; Mingdong Deng; Xinyu Zhang; Yueqi Wang; Wenyou Zhu; Tian Zeng; Wei Zheng; Yaping Wang; Min Gou; Zhaoxiang Wang (Bioresource Technology, 2026)

Augmented innate and humoral immune responses enhance early and durable rabies protection by a CD40L-overexpressing rabies vaccine - Xiao Xing; Yufang Wang; Zhimin Xiong; Die Liu; Yong Wang; Yang Hu; Yaping Liu; Yingying Li (Veterinary Microbiology, 2026)

Employment of magnetic measurements for monitoring conversion reactions in Fe3O4 anodes for lithium and sodium ion batteries - Bi Fu; Minghan Yang; Junfu Cheng; Zhanxu Chen; Yunbao Zheng; Yifang Li; Guangqi Hu; Yingji He; Chengzhi Hu; Yaping Wang (Chemical Engineering Journal, 2026)

Subduction-dominated processes control deep lithospheric structure and microplate tectonics of the Iranian Plateau: Insights from multi-geophysical inversions - Feiyu Zhao; Sanzhong Li; Junling Pei; Yanhui Suo; Mengxue Dai; Shengxing Zhang; Xiao Chen; Yanguo Wang; Yaping Hu; Bin Hu (Earth-Science Reviews, 2026)

Bioequivalence evaluation of risedronate sodium in healthy Chinese participants under fasting conditions: a randomized, open-label, single-dose, three-period, partial replicate crossover study - Ling He; Dan Hong; Weiyong Li; Yaping Hu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Characterizing rupture process and fault geometry of the 2017 Mw 6.5 Jiuzhaigou earthquake using potency density tensor inversion - Yaping Hu (Physics of the Earth and Planetary Interiors, 2026)

Optimization of extraction process for active component (dihydromyricetin) from industrial crop vine tea (Ampelopsis grossedentata) and its potential application in functional products for alleviating intestinal inflammation - Zhongxing Chu; Zuomin Hu; Jinping Ding; Yaping Zhou; Feijun Luo; Qinlu Lin (Food Bioscience, 2026)

Loss of foxp3a drives sex-specific immune-metabolic remodeling across the gut-liver-gonad axis in zebrafish - Yuhang Hu; Deinyefa Godfree Igbiriki; Nan Wu; Jialin Li; Junheng Liu; Jiuwu Yin; Jinping Duan; Xianmei Li; Zhixian Qiao; Feng Xiong; Yingyin Cheng; Wanting Zhang; et al. (Fish & Shellfish Immunology, 2026)

Promoting high energy density Mn-based layered oxide cathodes via surface structural regulation for sodium-ion batteries - Maohan Liu; Lingyi Kong; Xinyu Zhang; Yaping Yan; Haiyan Hu; Hanshen Xin; Jiayang Li; Yubin Niu; Yanfang Zhu; Yao Xiao (Chemical Engineering Journal, 2026)

The alkaloid-rich extract of Piper sintenense Hatusima alleviates gouty inflammatory response via Nrf2-mediated antioxidant induction - Zhiren Yao; Yu Su; Yaping Huang; Can Hu; Ke Pan; Jian Zhang; Guoqing Zhao; Lei Wang; Zhiqi Yin (Inflammopharmacology, 2026)

Exploring contributions and responses of microbial quantity and diversity to coastal seasonal hypoxia - Guihao Li; Jiarong Hu; Pengfei Zheng; Ping Zhu; Yaping Wang; Songbao Zou; Xiaoli Zhang; Eleni Gentekaki; Song Sun; Aolin Zhu; Jun Gong (Marine Pollution Bulletin, 2026)

Numerical study on the icing hazard zone of engine intake components under anti-icing conditions - Shuliang Jing; Yaping Hu; Jing Xu; Yuetao Jiang; Weiliang Zheng; Yaxin Du (Cold Regions Science and Technology, 2026)

Hydrogen production via gasification of corn stover photo-fermentation Residue: Catalytic mechanism of alkali metals - Kaixin Wang; Xiaoyu Yan; Yaping Zheng; Jiatao Dang; Sen Yao; Wei Wang; Panbo Yang; Shuheng Zhao; Jianjun Hu (Bioresource Technology, 2026)

SETD2 Improves Endothelial Function and Angiogenesis in Diabetic Hindlimb Ischemia Via Activating ANGPT2-PI3K/AKT Pathway - Langtao Wang; Qing Wang; Jiaxing Duan; Yu Tan; Yuanyuan Liu; Shuai Hu; Cheng Wang; Chen Yang; Yanzhu Long; Jinxuan Wang; Tao Yu; Tianhu Liu; et al. (Cardiovascular Toxicology, 2026)

Tuning CO2 separation of Type I UiO-66 porous liquids by varying the size of porous hosts - Shuangshuang Long; Jingwen Wang; Shuqian Meng; Yaxin Liu; Jing Zhang; Zihao Ren; Jiadi Li; Yangyang Xin; Zheng Dong; Baolu Cui; Libing Qian; Wenwu Zhou; et al. (Journal of Environmental Chemical Engineering, 2026)

Rainfall patterns and catchment characteristics interactively regulate nitrogen and phosphorus dynamics in agricultural ponds - Hengbin Xiao; Yaping Chen; Tianzi Hu; Ronggui Hu (CATENA, 2026)

Genomic insights into recurrent demographic collapses and recovery dynamics in Tibetan antelopes (Pantholops hodgsoni) - Weimin Kuang; Hongfeng Zhang; Yingli Jiang; Han Hu; Wei Huang; Yaping Zhang; Xiaomin Wu; Li Yu (Science China Life Sciences, 2026)

Targeting the gut-liver axis with dietary polyphenols to ameliorate metabolic dysfunction-associated steatotic liver disease: advances in molecular mechanisms - Zuomin Hu; Zeyu He; Yuyan Wang; Zhongxing Chu; Yaping Zhou; Wen Li; Jun Lu; Qinlu Lin; Feijun Luo (Critical Reviews in Food Science and Nutrition, 2026)

Corrigendum to ‘Gallic acid acts as an anti-inflammatory agent via PPARγ-mediated immunomodulation and antioxidation in fish gut-liver axis’ [Aquaculture 578 (2024) 740142] - Xuyang Zhao; Lei Zhang; Nan Wu; Yuhang Liu; Jiayuan Xie; Lian Su; Qingsong Zhu; Bruno Hamish Unger; Fatima Altaf; Yuhang Hu; Weidong Ye; Zhixian Qiao; et al. (Aquaculture, 2026)

Selective CO2 photoreduction to acetate enabled by charge-enriched interface sites confined in metal nanoclusters - Juncheng Zhu; Yang Wu; Jun Hu; Zijia Lin; Zexun Hu; Mingyu Wu; Runhua Chen; Kai Zheng; Wenxiu Liu; Bangwang Li; Junfa Zhu; Yang Pan; et al. (Science Bulletin, 2026)

An mRNA microsphere vaccine inhibiting overactivation of DNA sensing mechanisms - Fangke Zhang; Jiancheng Zheng; Fei Wang; Yaping Zhuang; Yunkai Tang; Juan Wang; Yawei Du; Wei-Li Zhao; Min Lu; Weiguo Hu; Wenguo Cui (Science Bulletin, 2026)

Spatiotemporal dynamics of microplastics in urban stormwater runoff: Functional area effects and transport pathways (Shanghai, China) - Junhao Li; Bowen Yu; Chengjin Cao; Liuxing Wu; Yaping Zhao; Ruiyun Zhu; Yangyang Hu; Minsheng Huang; Lei Wang; Xinlin Yan (Journal of Contaminant Hydrology, 2026)

Sedimentary dynamics in the subaqueous delta of the abandoned estuary: Effects of strong wave activity and riverine re-supply - Chaoran Lin; Longhai Zhu; Yaping Wang; Rui Bao; Rijun Hu; Lingpeng Meng (Marine Geology, 2026)

Grass carp (Ctenopharyngodon idella) Kat5 mediates P53 acetylation to induce apoptosis and promotes GCRV replication - Bao Liu; Chuxin Wu; Xianggao Meng; Tingting Yu; Xucheng Zhang; Jing Liu; Mingzhi Li; Yaping Weng; Huiling Mao; Chengyu Hu; Lingbao Kong; Meifeng Li (Fish & Shellfish Immunology, 2026)

Effect of PEDV infection on IPEC-J2 cells on miR-328–3p/FoxO4/NF-κB/MLCK signaling axis - Yiming Wei; Zixuan Qi; Yaping Shuai; Shihui Zhao; An Liu; Jiuyuan Liu; Di Bao; Han Zhao; Shuang Zhang; Hongze Shao; Shushuai Yi; Jiangting Niu; et al. (Veterinary Microbiology, 2025)

Deep insights into LDH reconstruction for enhanced capacitive deionization - Xiaohong Shang; Jinguo Hu; Yaping Yan; Siyu Li; Jiameng Diao; Haoyu Wang; Bin Hu; Hao Wang (Journal of Environmental Chemical Engineering, 2025)

Highly sensitive and wide-range quantification of bovine αS1-casein in foods for predicting potential milk allergenicity using an IgE multi-epitope-specific antibody - Caiyi Shen; Liming Li; Caiyun Long; Yunbiao Luo; Yaping Dong; Jinyu Yu; Yi Yao; Guanrong Hu; Xin Li; Hongbing Chen; Shengfa He (Food Chemistry, 2025)

Highly efficient biophotoelectrochemical methanogenesis coupling with water sterilization via robust interfacial electronic communication - Jing Hu; Chaohui Yang; Yaping Qi; Mingqiu Hong; Jiajing Chen; Guoping Ren; Jie Ye (Chemical Engineering Journal, 2025)

Corrigendum to “The role of ribosomal protein StRPS5 in mediating resistance of Solanum tuberosum plants to Phytophthora infestans” [Plant Sci. 357 (2025), 112539] - Jing Liu; Yaping Hu; Xiaoqing Lu; Jifen Xu; Hongyang Wang; Wei Tang; Canhui Li (Plant Science, 2025)

Corrigendum to “The role of ribosomal protein StRPS5 in mediating resistance of Solanum tuberosum plants to Phytophthora infestans“ [Plant Sci. 357 (2025) 112539] - Jing Liu; Yaping Hu; Xiaoqing Lu; Jifen Xu; Hongyang Wang; Wei Tang; Canhui Li (Plant Science, 2025)

Antibacterial photodynamic inactivation of pH-responsive microspheres based on chitosan/carboxymethyl chitosan with hypericin and its application in food preservation - Jingyi He; Sai Zhang; Zeyu Hu; Hetong Chen; Yaping Wang; Kewei Feng; Junfeng Yao; Yahong Yuan; Tianli Yue; Qinglin Sheng (Food Bioscience, 2025)

The role of ribosomal protein StRPS5 in mediating resistance of Solanum tuberosum plants to Phytophthora infestans - Jing Liu; Yaping Hu; Xiaoqing Lu; Jifen Xu; Hongyang Wang; Wei Tang; Canhui Li (Plant Science, 2025)

Condition assessment of corroded spanning subsea pipelines under vortex-induced vibration - Xinhong Li; Runquan Li; Yaping Hu; Ziyue Han; Xiuquan Liu; Yuanjiang Chang (Ocean Engineering, 2025)

Targeting Nrf2 by bioactive peptides alleviate inflammation: expanding the role of gut microbiota and metabolites - Zhongxing Chu; Lingfeng Zhu; Yaping Zhou; Feiyan Yang; Zuomin Hu; Yi Luo; Wen Li; Feijun Luo (Critical Reviews in Food Science and Nutrition, 2025)

Tyrosinase inhibition and enzyme kinetics of red rice bran protein peptides: Mechanism, identification, in silico exploration, and experimental validation - Zhenhao Zhao; Junbo Hu; Huimin Cui; Tianrui Zhao; Yaping Liu; Zhengxuan Wang; Guiguang Cheng (Food Bioscience, 2025)

Nonlinear Sliding-Mode Super-Twisting Reaching Law for Unmanned Surface Vessel Formation Control Under Coupling Deception Attacks - Yifan Wang; Qiang Zhang; Yaping Zhu; Yancai Hu; Xin Hu (Journal of Marine Science and Engineering, 2025)
In this paper, a nonlinear sliding-mode super-twisting reaching law algorithm is designed to address the problem of coupling interference under deception attacks and actuator physical faults in USV formations during cooperative mining operations of a USVs-ROVs system. First, a USV model with attacks and disturbances is established, and a leader–follower formation system is designed. Then, based on the reaching law, the state error dynamic chatter can be effectively solved when it is far away from and reaches the sliding surface; a nonlinear sliding super-twisting reaching law is designed to improve the chatter characteristics of the sliding surface. Furthermore, to solve the problems of low fitting accuracy regarding control anomaly information and the difficulty of fending off signal-data interference attacks, a nonlinear saturation fault-tolerant filtering mechanism and a nonlinear fitting factor are designed. Finally, the stability of the algorithm is verified through Lyapunov theory. Under the same coupling deception probability, the nonlinear sliding-mode super-twisting reaching law algorithm designed in this paper enables the leader ship and each follower ship to reach stability within about 12s, and the formation system maintains its formation while also improving the control accuracy of each individual ship.

Role of Bacillus atrophaeus B1 in gut on nicotine tolerance of the fall armyworm - Yaping Chen; Wenyuan Zhao; Yanfang Hu; Yao Chen; Yahong Li; Zhongxiang Sun; Yuerui Li; Rongchao Luo; Ewei Du; Furong Gui (Pesticide Biochemistry and Physiology, 2025)

Soil micro-food web composition determines soil fertility and crop growth - Yaping Lin; Qing Yi; Dandan Gao; Jiangnan Li; Wei Zhang; Kelin Wang; Dan Xiao; Peilei Hu; Jie Zhao (Soil Ecology Letters, 2025)

Comparative analysis of Seabuckthorn and its significant component in enhancing fish mucosal immunity - Yuhang Liu; Lian Su; Danying Cao; Nan Wu; Yuhang Hu; Fatima Altaf; Jialin Li; Qingsong Zhu; Junheng Liu; Qianqian Zhang; Haokun Liu; Yingyin Cheng; et al. (Aquaculture, 2025)

Tankyrase inhibitor IWR-1 modulates HIPPO and Transforming Growth Factor β signaling in primed bovine embryonic stem cells cultured on mouse embryonic fibroblasts - Yao Xiao; Yujie Wang; Minghao Zhang; Yan Zhang; Zhihua Ju; Jinpeng Wang; Yaran Zhang; Chunhong Yang; Xiuge Wang; Qiang Jiang; Yaping Gao; Xiaochao Wei; et al. (Theriogenology, 2025)

Landscape indices explain different responses of runoff and sediment yield to land use/cover change on the Loess Plateau, China - Yanli Qin; Peng Shi; Yuan Hu; Qiang Li; Yaping Wang; Qiaoqiao Wang; Duoduo Zhou (CATENA, 2025)

Targeting gut-liver axis by dietary lignans ameliorate obesity: evidences and mechanisms - Zhongxing Chu; Zuomin Hu; Yi Luo; Yaping Zhou; Feiyan Yang; Feijun Luo (Critical Reviews in Food Science and Nutrition, 2025)

Sinensetin from citrus peel alleviates DSS-induced inflammation by regulating gut microbiota and serum metabolism in mice - Zuomin Hu; Zhongxing Chu; Xuke Ling; Yuchi Wu; Dandan Qin; Feiyan Yang; Xudong Yu; Yaping Zhou; Yiping Tang; Feijun Luo (Food Bioscience, 2024)

ZnO nanoparticles induce melanoma-like lesions via recruiting dermal dendritic cells in barrier-damaged skin in mice - Menghan You; Yingying Huang; Yeda Chen; Dan Li; Yaping Tang; Yi kuan Du; Hong Yang; Anfa Liang; Guodong Hu; Yinghua Chen (Food and Chemical Toxicology, 2024)

Regulation of nitrogen metabolism by COE2 under low sulfur stress in Arabidopsis - Vincent Ninkuu; Yaping Zhou; Hao Liu; Susu Sun; Zhixin Liu; Yumeng Liu; Jincheng Yang; Mengke Hu; Liping Guan; Xuwu Sun (Plant Science, 2024)

Corrigendum to “Distribution of organophosphorus pesticides and its potential connection with probiotics in sediments of a shallow freshwater lake” [Journal of Contaminant Hydrology 261 (2024) 104306] - Yanping Hu; Rong Xiao; Yaping Wang; Junming Li; Congling Guo; Ling Zhang; Kegang Zhang; Milko A. Jorquera; Javiera Manquian; Wenbin Pan (Journal of Contaminant Hydrology, 2024)

Integrated transcriptomic, metabolomic, and functional analyses unravel the mechanism of bagging delaying fruit cracking of pomegranate (Punica granatum L.) - Yuying Wang; Yaping Hu; Hongfang Ren; Xueqing Zhao; Zhaohe Yuan (Food Chemistry, 2024)

Accumulation and ecological risk assessment of diazinon in surface sediments of Baiyangdian lake and its potential impact on probiotics and pathogens - Yaping Wang; Rong Xiao; Yanping Hu; Junming Li; Congling Guo; Ling Zhang; Kegang Zhang; Milko A. Jorquera; Wenbin Pan (Environmental Pollution, 2024)

Corrigendum to “Pathogen profile of Baiyangdian Lake sediments using metagenomic analysis and their correlation with environmental factors” [Sci. Total Environ. 913 (2024) 169628] - Rong Xiao; Yanping Hu; Yaping Wang; Junming Li; Congling Guo; Ling Zhang; Kegang Zhang; Milko A. Jorquera; Jacquelinne J. Acuña; Wenbin Pan (Science of The Total Environment, 2024)

Network pharmacology combined with molecular docking and molecular dynamic simulation to reveal the potential mechanism of lentinan ameliorating hyperlipidemia - Zhongxing Chu; Linna Zeng; Feiyan Yang; Zuomin Hu; Yi Luo; Yaping Zhou; Yiping Tang; Feijun Luo (Food Bioscience, 2024)

Machine learning framework develops neutrophil extracellular traps model for clinical outcome and immunotherapy response in lung adenocarcinoma - A. Xuan Han; B. Yaping Long; C. Yao Li; D. Di Huang; E. Qi Xiong; F. Jinfeng Li; G. Liangliang Wu; Qiaowei Liu; G. Bo Yang; H. Yi Hu (Apoptosis, 2024)

Microglial exosomes in paraquat-induced Parkinson's disease: Neuroprotection and biomarker clues - Jingwen Wu; Wenya Shao; Xu Liu; Fuli Zheng; Yaping Wang; Ping Cai; Zhenkun Guo; Hong Hu; Guangxia Yu; Jianhui Guo; Linlin Yao; Siying Wu; et al. (Environmental Pollution, 2024)

Effect of complex prebiotics on Lactobacillus gasseri JM1 fermented soymilk: Physicochemical, flavor characteristics, and metabolites - Yaping Zheng; Wenfang Wu; Man Zhu; Yilin Sun; Dong Hu; Yujun Jiang; Yu Zhang; Chaoxin Man (Food Bioscience, 2024)

Super absorbent resilience antibacterial aerogel with curcumin for fresh pork preservation - Fangqu Wang; Zipeng Xu; Lin Chen; Ziyan Qiao; Yayun Hu; Xiaojing Fan; Yaping Liu; Zhuangli Kang; Feng Huang; Minyi Han; Huijuan Yang; Xianchao Feng (Food Control, 2024)

Optical sensors of volatile organic compounds for non-invasive diagnosis of diseases - Xiaoyun Qu; Yaping Hu; Chenggang Xu; Yue Li; Lin Zhang; Qiao Huang; Sareh Sadat Moshirian-Farahi; Jianmin Zhang; Xiahong Xu; Ming Liao; Yingchun Fu (Chemical Engineering Journal, 2024)

Chemically tailored molecular surface modification of bamboo pulp fibers for manipulating the electret performance of electret filter media - Chunxia Pang; Huanhuan You; Sijie Lei; Fan Su; Lili Liang; Zhanguo Li; Xiaoyan Lin; Yaping Zhang; Hao Zhang; Xunhai Pan; Yang Hu (Carbohydrate Polymers, 2024)

Pathogen profile of Baiyangdian Lake sediments using metagenomic analysis and their correlation with environmental factors - Rong Xiao; Yanping Hu; Yaping Wang; Junming Li; Congling Guo; Junhong Bai; Ling Zhang; Kegang Zhang; Milko A. Jorquera; Jacquelinne J. Acuña; Wenbin Pan (Science of The Total Environment, 2024)

Distribution of organophosphorus pesticides and its potential connection with probiotics in sediments of a shallow freshwater lake - Yanping Hu; Rong Xiao; Yaping Wang; Junming Li; Congling Guo; Junhong Bai; Ling Zhang; Kegang Zhang; Milko A. Jorquera; Javiera Manquian; Wenbin Pan (Journal of Contaminant Hydrology, 2024)

Gallic acid acts as an anti-inflammatory agent via PPARγ-mediated immunomodulation and antioxidation in fish gut-liver axis - Xuyang Zhao; Lei Zhang; Nan Wu; Yuhang Liu; Jiayuan Xie; Lian Su; Qingsong Zhu; Bruno Hamish Unger; Fatima Altaf; Yuhang Hu; Weidong Ye; Zhixian Qiao; et al. (Aquaculture, 2024)

Reproductive hormones, organophosphate esters and semen quality: Exploring associations and mediation effects among men from an infertility clinic - Yaping Li; Zhiyi Zheng; Dan Luo; Chong Liu; Sijie Yang; Yingjun Chen; Qian Hu; Wenqing Lu; Yixin Wang; Surong Mei (Environmental Research, 2024)

A step closer to real practice: Integrated tandem photocatalysis-biofilm process towards degradation of crude oil - Xin Hu; Yaping Pan; Shanshan Zhao; Feifei Zhang; Fengshu Li; Zhe Li; Haoshuai Li; Yiming Li; Jinren Lu; Xiaolong Yang; Mutai Bao (Journal of Environmental Management, 2023)

Protective effect of hot-water and ethanol-aqueous extracts from Anneslea fragrans against acetaminophen-induced acute liver injury in mice - Yiwen Hu; Mengcheng Li; Yongpeng Wang; Qingwang Xue; Xiaodong Luo; Afsar Khan; Tianrui Zhao; Yaping Liu; Zhengxuan Wang; Yudan Wang; Guiguang Cheng (Food and Chemical Toxicology, 2023)

Fine lithospheric structure controlling Meso-Cenozoic tectono-magmatism in the South China Block: Inference from a multidisciplinary analysis - Feiyu Zhao; Yanhui Suo; Lijun Liu; Xianzhi Cao; Sanzhong Li; Suhua Jiang; Juzhi Deng; Mengxue Dai; Ying Liu; Yaping Hu; Shuzhong Sheng; Bin Hu (Earth-Science Reviews, 2023)

Uncovering the dynamic evolution of microbes and n-alkanes: Insights from the Kuroshio Extension in the Northwest Pacific Ocean - Xin Hu; Xinping Wang; Shanshan Zhao; Lixin Cao; Yaping Pan; Fujuan Li; Fengshu Li; Jinren Lu; Yiming Li; Guodong Song; Honghai Zhang; Peiyan Sun; et al. (Science of The Total Environment, 2023)

A mechanically soft-tissue-like organohydrogel with multi-functionalities for sensitive soft ionotronics - Shuxiang Liu; Yuping Chen; Jin Feng; Junjie Peng; Yaping Zhou; Yang Zhao; Yongpeng Zhao; Zhiwei Lu; Mengmeng Sun; Chun Wu; Haipeng Hu; Hanbing Rao; et al. (Chemical Engineering Journal, 2023)

Lacticaseibacillus casei LH23 Suppressed HPV Gene Expression and Inhibited Cervical Cancer Cells - Shiyue Hu; Yunpeng Hao; Xiao Zhang; Yaping Yang; Meiling Liu; Nan Wang; Tong-Cun Zhang; Hongpeng He (Probiotics and Antimicrobial Proteins, 2023)

Independent and combined effects of exposure to organophosphate esters on thyroid hormones in children and adolescents - Liqin Hu; Bin Zhou; Yaping Li; Lulu Song; Jin Wang; Meng Yu; Xiang Li; Ling Liu; Jing Kou; Youjie Wang; Xijiang Hu; Surong Mei (Environmental Geochemistry and Health, 2023)

The association between organophosphate esters exposure and body mass index in children and adolescents: The mediating effect of sex hormones - Yaping Li; Liqin Hu; Bin Zhou; Zhiyi Zheng; Qitong Xu; Jun Liu; Lulu Song; Youjie Wang; Surong Mei (Chemosphere, 2023)

Neural Network, Nonlinear-Fitting, Sliding Mode, Event-Triggered Control under Abnormal Input for Port Artificial Intelligence Transportation Robots - Yaping Zhu; Qiang Zhang; Yang Liu; Yancai Hu; Sihang Zhang (Journal of Marine Science and Engineering, 2023)
A new control algorithm was designed to solve the problems of actuator physical failure, remote network attack, and sudden change in trajectory curvature when a port’s artificial intelligence-based transportation robots track transportation in a freight yard. First of all, the nonlinear, redundant, saturated sliding surface was designed based on the redundant information of sliding mode control caused by the finite nature of control performance; the dynamic acceleration characteristic of super-twisted sliding mode reaching law was considered to optimize the control high frequency change caused by trajectory mutation; and an improved super-twist reaching law was designed. Then, a nonlinear factor was designed to construct a nonlinear, fault-tolerant filtering mechanism to compensate for the abnormal part of the unknown input that cannot be executed by adaptive neural network reconstruction. On this basis, the finite-time technology and parameter-event-triggered mechanism were combined to reduce the dependence on communication resources. As a result, the design underwent simulation verification to verify its effectiveness and superiority. In the comparative simulation, under a consistent probability of a network attack, the tracking accuracy of the algorithm proposed in this paper was 22.65%, 12.69% and 11.48% higher those that of the traditional algorithms.

TCR repertoire landscape reveals macrophage-mediated clone deletion in endotoxin tolerance - Juanjuan Zhao; Li Jia; YiJing Tao; Xu Zhao; Jing Yang; Yanxin Lu; Yaping Yan; Ling Mao; Lin Hu; Jia Lu; MengMeng Guo; Chao Chen; et al. (Inflammation Research, 2023)
Background Endotoxin tolerance (ET) is a protective mechanism in the process of sepsis, septic shock, and their sequelae including uncontrolled inflammation. Accumulating evidence has shown that peripheral T cells contribute to the induction of ET. However, what and how T-cell development contributes to ET inductions remain unclear. Methods Mice were intraperitoneally injected with LPS at a concentration of 5 mg/kg to establish an LPS tolerance model and were divided into two groups: a group examined 72 h after LPS injection (72-h group) and a group examined 8 days after LPS injection (8-day group). Injection of PBS was used as a control. We performed high-throughput sequencing to analyze the characteristics and changes of CD4 + SP TCR β CDR3 repertoires with respect to V direct to J rearrangement during the ET induction. Moreover, the proportion and proliferation, as well as surface molecules such as CD80 and CD86, of F4/80 + macrophages were analyzed using FCM. Furthermore, ACT assay was designed and administered by the tail vein into murine LPS-induced mouse model to evaluate the role of F4/80 + macrophages on the development of CD4 + SP thymocytes in ET condition. Results We found that the frequency and characteristics of the TCR β chain CDR3 changed obviously under condition of ET, indicating the occurrence of TCR rearrangement and thymocyte diversification. Moreover, the absolute numbers of F4/80 + macrophages, but not other APCs, were increased in thymic medulla at 72-h group, accompanied by the elevated function-related molecules of F4/80 + macrophages. Furthermore, adoptively transferred OVA 332-339 peptide-loaded macrophages into Rag-1 −/− mice induced the clone deletion of OVA-specific CD4 + SP, thereby ameliorating the pathology in lung tissue in LPS challenge. Conclusions These data reveal that the frequency and characteristics of the TCR β chain CDR3 undergo dynamic programming under conditions of LPS tolerance. Furthermore, the peripheral macrophages may be a key factor which carry peripheral antigen to thymic medulla and affect the negative selection of T-cell population, thereby contributing to the formation of ET. These results suggest that the clone selection in thymus in ET may confer protection against microbial sepsis.

Disruption of phosphate metabolism and sterol transport-related genes conferring yeast resistance to vanillin and rapid ethanol production - Fengguang Zhao; Yaping Zhang; Jian Hu; Ce Shi; Xiang Ao; Shengding Wang; Ying Lin; Zhongwei Sun; Shuangyan Han (Bioresource Technology, 2023)

Assessment of Fungal Diversity in Minqin County, a Typical Arid Region in Northwestern China - Zhanwu Peng; Shuwei Wei; Yaping Hu; Bao Qi; Chaofeng Yuan; Qi Wang; Yu Li (Current Microbiology, 2023)

Spatial and temporal characteristics of nighttime UHII based on local climate zone scheme using mobile measurement-A case study of Changsha - Yaping Chen; Jiayu Li; Yinze Hu; Luyun Liu (Building and Environment, 2023)

Correction to: Alpinia officinarum mediated copper oxide nanoparticles: synthesis and its antifungal activity against Colletotrichum gloeosporioides - Chunmei Hu; Wenjia Zhu; Ying Lu; Yanfang Ren; Jinyu Gu; Yaping Song; Junyu He (Environmental Science and Pollution Research, 2022)

Alpinia officinarum mediated copper oxide nanoparticles: synthesis and its antifungal activity against Colletotrichum gloeosporioides - Chunmei Hu; Wenjia Zhu; Ying Lu; Yanfang Ren; Jinyu Gu; Yaping Song; Junyu He (Environmental Science and Pollution Research, 2022)

The structure, characterization and dual-activity of exopolysaccharide produced by Bacillus enclensis AP-4 from deep-sea sediments - Xin Hu; Fengshu Li; Xiuli Zhang; Yaping Pan; Jinren Lu; Yiming Li; Mutai Bao (Frontiers in Marine Science, 2022)
In recent years, the exopolysaccharide (EPS) produced by deep-sea bacteria has attracted the interest of various researchers. In the present study, we have explored the properties and structure of a novel exopolysaccharide (called BPS) produced by Bacillus enclensis AP-4 from deep-sea sediments. The maximum yield of BPS was 4.23 ± 0.17 g L −1 in a 2216E modified medium. 1 H NMR studies of the purified BPS displayed α and β-configuration sugar residues, including mannose, glucosamine, glucose, galactose, and xylose in a molar ratio of 1.00: 0.09: 0.04: 0.09: 0.07. BPS showed a molecular weight of 23,434 Da and was abundant in hydroxyl and amino residues. In addition, BPS exhibited a rod-like structure with a rough surface and was dominated by C, N, and O elements. The exopolysaccharide demonstrated remarkable thermal stability, high degradation temperature, and excellent emulsification capacity compared to most reported exopolysaccharides. Moreover, BPS displayed better quenching activities against the four radicals, which provided favorable protection for the strain. Finally, the freezing experiment investigated the cryoprotective effect of BPS on E. coli and S. aureus . BPS effectively improved the cell survival ratio and maintained the activity of Na + /K + -ATPase, which facilitates culture preservation. To the best of our knowledge, our work is the first report suggesting that marine exopolysaccharide has dual-activity. This work presents the foundation for the analysis of the structure and properties of exopolysaccharides produced by deep-sea bacteria.

Induced mutation in ELONGATED HYPOCOTYL5 abolishes anthocyanin accumulation in the hypocotyl of pepper - Rong Chen; Can Yang; Hu Gao; Chunmei Shi; Zhiying Zhang; Guangyu Lu; Xinyan Shen; Yaping Tang; Feng Li; Yongen Lu; Bo Ouyang (Theoretical and Applied Genetics, 2022)

Dynamic Damping-Based Terminal Sliding Mode Event-Triggered Fault-Tolerant Pre-Compensation Stochastic Control for Tracked ROV - Qiyu Chen; Yancai Hu; Qiang Zhang; Junpeng Jiang; Mingshan Chi; Yaping Zhu (Journal of Marine Science and Engineering, 2022)
Due to the unknown disturbance caused by the harsh environment in deep water, the stability of Underwater Tracked Remotely Opreated Vehicle (UTROV) trajectory tracking control is affected; especially the resistance forces of random vibrations caused by non-differentiable random disturbance resistance, which has become one of the main problems in controller design. Considering engineering practice, a stochastic model and new dynamic damping-based terminal sliding mode event-triggered fault-tolerant controller were designed in this paper. Firstly, based on the random resistance pre-compensation theory for the first time, a stochastic model was designed for differential drive UTROV. Meanwhile, a new nonsingular terminal sliding mode and dynamic damping reaching law were designed to achieve global finite-time convergence and reduce chattering with better robust response speed. Furthermore, to deal with the wear and tear caused by actuator failure and fixed sampling rate transmission, a new dynamic event trigger mechanism was designed and the faults analyzed. On this basis, combined with the finite-time adaptive on-line estimation technology, it can not only better reduce the transmission frequency, but also the finite-time dynamic active fault-tolerant compensation. The control scheme has semi-globally finite-time stability in probability and is proved by theory, which is compliant with engineering requirements. Then, according to characteristics of innovation, the three groups of simulation of control methods are designed to compare the methods in this paper. Finally the advantages of the method are verified by simulation to achieve the design expectations.

Organophosphate esters in children and adolescents in Liuzhou city, China: concentrations, exposure assessment, and predictors - Meng Yu; Xiang Li; Bingqing Liu; Yaping Li; Ling Liu; Limei Wang; Lulu Song; Youjie Wang; Liqin Hu; Surong Mei (Environmental Science and Pollution Research, 2022)

Soil phosphorus availability and stoichiometry determine microbial activity and functional diversity of fluvo-aquic soils under long-term fertilization regimes - Wei He; Wenhua Ye; Mingjie Sun; Yaping Li; Manman Chen; Meng Wei; Guoqing Hu; Quangang Yang; Hong Pan; Yanhong Lou; Hui Wang; Yuping Zhuge (Journal of Soils and Sediments, 2022)

Biological monitoring and health assessment of 21 metal(loid)s in children and adolescents in Liuzhou City, Southwest China - Yaping Li; Yu Zhang; Meng Yu; Liqin Hu; Ting Zeng; Ling Liu; Limei Wang; Liangqiong Deng; Xiang Li; Ping Liu; Dingyuan Zeng; Surong Mei (Environmental Science and Pollution Research, 2022)

A 90-Day Subchronic Toxicity Study of Consumption of GH-Transgenic Triploid Carp in Wistar Rats - Jingya Guo; Yongming Li; Yaping Wang; Boyong Chen; Yingxin Hu; Yasheng Musha; Xiaoyun He; Tao Tong; Kunlun Huang (Fishes, 2022)
Genetic modification (GM) offers an alternative strategy to conventional animal breeding. The present study was carried out to investigate the potential health effects of the consumption of growth hormone-transgenic triploid carp (GH-ttc) through a 90-day subchronic rodent feeding study. Wistar rats (n = 10/sex/group) were given formulated diets containing GH-ttc or non-GM carp at an incorporated rate of 2.5%, 5%, or 10% (w/w) for 90 days. An additional control group of rats (n = 10/sex/group) was fed a basic rodent diet. During the 90-day study, clinical observation, ophthalmic examination, body weight, and food intake were evaluated. At the end of the study, rats were killed, and the hematology, serum chemistry, urine test, necropsy, and histopathology were assessed. Compared with the non-GM carp and the basic control groups, no biologically significant differences were observed on clinical signs of toxicity, body weights, food intake, hematology, serum chemistry, urinalysis, organ weight, and histopathology on selected organs for the GH-ttc group. The results of this 90-day subchronic feeding study indicated that, at the dose level used in this study, consumption of GH-ttc showed no subchronic toxicity to Wistar rats.

ADV-Based Investigation on Bed Level Changes Over a Meso-Macro Tidal Beach - Wenhong Pang; Xiaoyan Zhou; Zhijun Dai; Shushi Li; Hu Huang; Yaping Lei (Frontiers in Marine Science, 2021)
Beach intra-tidal bed level changes are of significance to coastal protection amid global climate changes. However, due to the limitation of instruments and the disturbance induced by wave motions superimposed on water levels, it was difficult to detect the high-frequency oscillation of the submerged beach bed level. In this study, an observation, lasting for 12 days and covering the middle tide to the following spring tide, was conducted on a meso-macro tidal beach, Yintan Beach, to simultaneously detect the characteristics and influence mechanism of bed level changes at intra-tidal and tidal cycle scales. The collected data included water depth, suspended sediment concentration (SSC), waves, high-frequency three-dimensional (3-D) velocity, and the distance of the seabed to the acoustic Doppler velocimeter (ADV) probe, which were measured by an optical backscatter sensor, two Tide & Wave Recorder-2050s, and an ADV, respectively. The results showed that the tidal cycle-averaged bed level decreased by 58.8 mm, increased by 12.6 mm, and increased by 28.9 mm during neap, middle, and spring tides in succession, respectively, compared with the preceding tidal regimes. The net erosion mainly resulted from large incident wave heights and the consequent strong offshore-directed sediment transport induced by undertows. Moreover, the variations in the bed level were more prominent during a neap to middle tides than during middle to spring tides, which were jointly caused by the wave-breaking probability regulated by water depth and the relative residence times of shoaling wave, breaker, and surf zones that were determined by relative tidal range. In terms of the intra-tidal bed level, it displayed an intra-tidal tendency of increase during floods and decrease during ebb tides, i.e., the intra-tidal bed level changes were controlled by water depth, which modulated the effects of waves on sediment resuspension and vertical sediment exchange. To be specific, waves and SSC were responsible for the intra-tidal bed level changes under low-energy wave conditions, while mean current and bedform exerted important influences on the variations of the intra-tidal bed level under moderate wave conditions, which broke the foregoing interrelation between bed level, waves, and SSC. This study, therefore, emphasizes the usage of ADV measurement to investigate bed level changes in sandy coasts.

Proteomic analysis of the exosomes secreted from Ctenopharyngodon idellus kidney cells infected with grass carp reovirus reveals their involvement in the cellular responses to viral infection - Xing Zhang; Yunshan Zhang; Jun Pan; Min Zhu; Zi Liang; Zeen Shen; Kun Dai; Bingyu Yan; Yaping Dai; Renyu Xue; Guangli Cao; Xiaolong Hu; et al. (Fish Physiology and Biochemistry, 2021)

Divergent shrub‐cover responses driven by climate, wildfire, and permafrost interactions in Arctic tundra ecosystems - Yaping Chen; Feng Sheng Hu; Mark J. Lara (Global Change Biology, 2021)
The expansion of shrubs across the Arctic tundra may fundamentally modify land–atmosphere interactions. However, it remains unclear how shrub expansion pattern is linked with key environmental drivers, such as climate change and fire disturbance. Here we used 40+ years of high‐resolution (~1.0 m) aerial and satellite imagery to estimate shrub‐cover change in 114 study sites across four burned and unburned upland (ice‐poor) and lowland (ice‐rich) tundra ecosystems in northern Alaska. Validated with data from four additional upland and lowland tundra fires, our results reveal that summer precipitation was the most important climatic driver ( r = 0.67, p p r = 0.83, p 2 ha −1 , ~7 times the amount identified in adjacent unburned upland tundra (155.1 ± 55.4 m 2 ha −1 ). In contrast, shrub cover markedly decreased in lowland tundra after fire disturbance, which triggered thermokarst‐associated water impounding and resulted in 52.4% loss of shrub cover over three decades. No correlation was found between lowland shrub cover with fire severity ( r = 0.01). Mean summer air temperature (MSAT) was the principal factor driving lowland shrub‐cover dynamics between 1951 and 2007. Warmer MSAT facilitated shrub expansion in unburned lowlands ( r = 0.78, p r = −0.82, p

De novo transcriptome of the whole-body of the gastropod mollusk Philomycus bilineatus, a pest with medical potential in China - Zhongjie Li; Yaping Yuan; Miaomiao Meng; Ping Hu; Yong Wang (Journal of Applied Genetics, 2020)

Review of Chinese atmospheric science research over the past 70 years: Synoptic meteorology - Zhiyong Meng; Fuqing Zhang; Dehai Luo; Zhemin Tan; Juan Fang; Jianhua Sun; Xueshun Shen; Yunji Zhang; Shuguang Wang; Wei Han; Kun Zhao; Lei Zhu; et al. (Science China Earth Sciences, 2019)

Identification of Potential Biomarkers with Diagnostic Value in Pituitary Adenomas Using Prediction Analysis for Microarrays Method - Hu Peng; Yue Deng; Longhao Wang; Yin Cheng; Yaping Xu; Jianchun Liao; Hao Wu (Journal of Molecular Neuroscience, 2019)

Laboratory experiments demonstrate that the hissing of the Chinese alligator can effectively inhibit movement of flower fish Ptychobarbus kaznakovi - Guoyong Liu; Yujiao Wu; Xiujun Shen; Yaping Hu; XiHuo Qin; Weixin Tian; Liming Liu; Xiaoling Wang; Xiaotao Shi (Hydrobiologia, 2019)

Preliminarily study on the maximum handling size, prey size and species selectivity of growth hormone transgenic and non-transgenic common carp Cyprinus carpio when foraging on gastropods - Tingbing Zhu; Lihong Zhang; Tanglin Zhang; Yaping Wang; Wei Hu; Rolf Eric Olsen; Zuoyan Zhu (Journal of Oceanology and Limnology, 2018)

LncRNA Gm2044 highly expresses in spermatocyte and inhibits Utf1 translation by interacting with Utf1 mRNA - Ke Hu; Leina Li; Yaping Liao; Meng Liang (Genes & Genomics, 2018)

Bacterial community temporal dynamics and disease-related variations in the seawater of Pyropia (laver) seedling pools - Xiangyu Guan; Wei Zhou; Chuanming Hu; Miaoxian Zhu; Yaping Ding; Shanshan Gai; Xiaoxuan Zheng; Jianyi Zhu; Qinqin Lu (Journal of Applied Phycology, 2018)

Applicability of Perinereis aibuhitensis Grube for fish waste removal from fish cages in Sanggou Bay, P. R. China - Jinghui Fang; Zengjie Jiang; Henrice M. Jansen; Fawen Hu; Jianguang Fang; Yi Liu; Yaping Gao; Meirong Du (Journal of Ocean University of China, 2017)

Novel rice mutants overexpressing the brassinosteroid catabolic gene CYP734A4 - Wenjing Qian; Chao Wu; Yaping Fu; Guocheng Hu; Zhengquan He; Wenzhen Liu (Plant Molecular Biology, 2017)

A Brachypodium distachyon MAPKK Gene BdMKK6.2 Negatively Regulates Drought Stress Tolerance in Transgenic Tobacco Plants - Jiutong Sun; Run Zhou; Yaping Li; Wei Hu; Ding Qiu; Xiatian Wang; Qiong Wang; Zhijuan Feng; Lianzhe Wang; Yi Zhou; Guangyuan He; Guangxiao Yang (Journal of Plant Growth Regulation, 2016)

The Brachypodium distachyon BdWRKY36 gene confers tolerance to drought stress in transgenic tobacco plants - Jiutong Sun; Wei Hu; Run Zhou; Lianzhe Wang; Xiatian Wang; Qiong Wang; Zhijuan Feng; Yaping Li; Ding Qiu; Guangyuan He; Guangxiao Yang (Plant Cell Reports, 2015)

Efficient Knockout of Transplanted Green Fluorescent Protein Gene in Medaka Using TALENs - Chao Qiu; Bin Cheng; Yunsheng Zhang; Rong Huang; Lanjie Liao; Yongming Li; Daji Luo; Wei Hu; Yaping Wang (Marine Biotechnology, 2014)

Development and characterization of 42 novel polymorphic microsatellite markers for Odontobutis potamophila from EST sequences - Lijuan Zhang; Hongwei Zhang; Yaping Zhang; Fei Zhu; Xinyuan Hou; Yali Hu; Shaowu Yin (Conservation Genetics Resources, 2014)

Enlargement of anode for enhanced simultaneous azo dye decolorization and power output in air-cathode microbial fuel cell - Jian Sun; Youming Li; Yongyou Hu; Bin Hou; Qian Xu; Yaping Zhang; Sizhe Li (Biotechnology Letters, 2012)

Vitreoscilla Hemoglobin (VHb) Overexpression Increases Hypoxia Tolerance in Zebrafish (Danio rerio) - Bo Guan; Hong Ma; Yaping Wang; Yuanlei Hu; Zhongping Lin; Zuoyan Zhu; Wei Hu (Marine Biotechnology, 2011)

Poly(ε-caprolactone)-Block-poly(ethyl Ethylene Phosphate) Micelles for Brain-Targeting Drug Delivery: In Vitro and In Vivo Valuation - Pengcheng Zhang; Luojuan Hu; Yucai Wang; Jun Wang; Linyin Feng; Yaping Li (Pharmaceutical Research, 2010)

Isolation and characterization of a rice mutant with narrow and rolled leaves - Chao Wu; Yaping Fu; Guocheng Hu; Huamin Si; Shihua Cheng; Wenzhen Liu (Planta, 2010)

Identification and characterization of HTD2: a novel gene negatively regulating tiller bud outgrowth in rice - Wenzhen Liu; Chao Wu; Yaping Fu; Guocheng Hu; Huamin Si; Li Zhu; Weijiang Luan; Zhengquan He; Zongxiu Sun (Planta, 2009)

Toll-like receptor 3 regulates Mx expression in rare minnow Gobiocypris rarus after viral infection - Jianguo Su; Zuoyan Zhu; Yaping Wang; Jun Zou; Wei Hu (Immunogenetics, 2008)

Identification and fine mapping of a thermo-sensitive chlorophyll deficient mutant in rice (Oryza sativa L.) - Wenzhen Liu; Yaping Fu; Guocheng Hu; Huamin Si; Li Zhu; Chao Wu; Zongxiu Sun (Planta, 2007)

Genetic Diversity of Yunnan Local Pig Breeds Inferred from Blood Protein Electrophoresis - Wenping Hu; Linsheng Lian; Bing Su; Yaping Zhang (Biochemical Genetics, 1998)